State bank transformation in Brazil – choices and consequences - Beck, Thorsten; Crivelli, Juan Miguel; Summerhill, William (Journal of Banking & Finance, 2005)
This paper analyzes the different options – liquidation, federalization, privatization and restructuring – that the Brazilian state governments had for the transformation of their state banks under the PROES in the late 1990s. Specifically, this paper explores (i) the factors behind the states’ choices and (ii) the effects of the transformation process on bank performance and efficiency. We find that states that were more dependent on federal transfers, whose banks were already under federal intervention and that established development agencies, were more likely to relinquish control over their banks and its transformation process. We find that privatized banks increased their performance, while restructured banks did not.